Developing eco-tourism and nature reserves in Kandil region using RS&GIS - رشید, دي. شيروان عمر رشيد; محمد, محمد وتمان محمد; ناصر, سەلام محمود ناصر (Sulaimani Journal for Humanities, 2025)
Qandil Region is located in the north and east of the Kurdistan Region. It possesses many natural and environmental characteristics that can be utilized for ecotourism activities and the establishment of nature reserves. However, tourism in the region is underdeveloped, and Qandil remains a hidden area in terms of tourism, with few visitors. Therefore, conducting research to identify obstacles, propose solutions, and highlight the environmental potential of the region is essential for ecotourism development. The main problem addressed in this study is the lack of attention and investment in the natural foundations of tourism development, which are essential to promoting environmental tourism and establishing nature reserves. The aim of this research is to collect data and create a geographic database to demonstrate the application and importance of natural principles in developing ecotourism activities and constructing nature reserves in the region. To achieve this, we will employ several scientific methods, including descriptive and comparative analysis, literature review, survey distribution, and the use of advanced Multi-Criteria Decision Analysis- Analytic Hierarchy Process (MCDA-AHP) through Remote Sensing (RS) and Geographic Information System (GIS) applications to attract tourism and identify optimal locations for nature reserves. One of the most important results of using the method is that 74% of the area of the area is at a good level to become a natural protected area
Keywords: Qandil; Ecotourism; Nature Reserve; RS GIS; MCDAAHP